Quantitative assessment of aldehydes in air and rainwater: a case study in natural conservation area of Costa Rica - Araya-Araya, Melissa (2023)
Aldehydes in the environment are among most organic compounds that participate in photochemical reactions, mainly forming radicals in significant quantities. These have harmful effects on the health of the inhabitants of cities with polluted atmospheres, mainly formaldehyde and acetaldehyde. In the present work, the concentration of seven aldehydes in air and rainwater samples in a conservation area of Costa Rica (Los Cusingos Biological Reserve, located in the South Pacific, Pérez Zeledón) was determined during 2017. For the sampling and analysis of the aldehydes, the TO-11A (EPA) method was used. Sampling used adsorption cartridges coated with a 2,4-dinitrophenylhydrazine (2,4-DNFH) solution. The samples were quantified by means of a liquid chromatograph coupled to a UV-Visible detector. The highest aldehyde concentrations in air samples correspond to formaldehyde (62.2 ± 3.1 μg/m3), acetaldehyde (88.1 ± 4.9 μg/m3) and acrolein (102.2 ± 5.2 μg/m3) during 4 hours of sampling. Heptanal was determined to be the least contributory aldehyde, as it was below the detection limit. The only aldehyde quantified in the rainwater samples was formaldehyde. The results obtained in the air sample suggest an increase in the concentration of aldehydes correlated with solar radiation and temperature, suggesting as the main contributor the photochemical reactions that take place in the air with precursor hydrocarbons.